2018
DOI: 10.1039/c8nj03794a
|View full text |Cite
|
Sign up to set email alerts
|

Designed functionalization of reduced graphene oxide for sorption of Cr(vi) over a wide pH range: a theoretical and experimental perspective

Abstract: The present study illustrates a clear functionalization chemistry for the synthesis of guanidine functionalized reduced graphene oxide (GfG) for sorption of Cr(VI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“…As shown in Figure 5, the adsorption energy of Cr(VI) is 290.32 kcal mol −1 , which indicates the presence of strong adsorptive interaction between the GO surface and the Cr(VI). The adsorption energy values are comparable with those found in the previous studies (where a different and a smaller GO model is used) [34]. It is important to observe that as computed by DFT calculation, the preferred adsorption site of the Cr(VI) is also predicted by MC.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As shown in Figure 5, the adsorption energy of Cr(VI) is 290.32 kcal mol −1 , which indicates the presence of strong adsorptive interaction between the GO surface and the Cr(VI). The adsorption energy values are comparable with those found in the previous studies (where a different and a smaller GO model is used) [34]. It is important to observe that as computed by DFT calculation, the preferred adsorption site of the Cr(VI) is also predicted by MC.…”
Section: Resultssupporting
confidence: 86%
“…It is important to observe that as computed by DFT calculation, the preferred adsorption site of the Cr(VI) is also predicted by MC. This is associated with the fact that electrostatic interactions can take place at this adsorption site as found previously by Mondal et al [34].…”
Section: Resultssupporting
confidence: 71%
“…Using a closely related approach, Nkutha et al [157] have made graphene-based sorbents by modification of graphene oxide with amino-and mercaptosilanes providing materials with -NH2 and -SH functional groups suitable for metal binding. The main outcome of the article is the observation that, analogous to the work by Mondal et al [156], the highest adsorption efficiencies were observed at pH 2. Again, the issue that could be raised here is that neither graphene nor specific silanes are necessarily very cheap; there is thus a need to further transfer these reactions and concepts to cheaper and more readily available carbon materials.…”
Section: Biomass and Carbonaceous Materialssupporting
confidence: 60%
“…Interestingly, the surface areas of these materials are below 100 m 2 /g. The materials show an excellent to carbon-based materials such as those discussed above [153][154][155][156][157][158][159], which show high adsorption capacities at low pH but perform rather poorly at high pH.…”
Section: Compositesmentioning
confidence: 93%
See 1 more Smart Citation